Muhammad Iqbal's Philosophy of Khudi (A Critical Analysis of Modern Science) - Hidayat, Alfan; Alamsah, Johan (Universitas Islam Negeri Raden Intan Lampung, 2024)
Abstract;Science is one of the most significant factors in approaching and identifying objects. It requires the foundation of actual self-awareness, such as understanding Khudi. The path of modernity and the increasing spirit of the Western Renaissance forced modern science to behave fragmentarily. As a result, the physical dimension is distinct from the metaphysical dimension, which is defined by values and morals. Therefore, this research aims to examine specific characteristics and perspectives of modern science, which will then be critiqued through the perspective of Muhammad Iqbal's Khudi philosophy. The study is library research with a philosophical approach, assessing the data critically. According to the findings of this study, Muhammad Iqbal's Khudi has a comprehensive-integral effect on a person by reviewing his consciousness. Thus, this philosophy provides universality, wise judgment, and a positive life connection from a philosophical standpoint, particularly for our era of scientific developments that serve as a reference for modern living.Keywords:Khudi; Modern; Renaissance; Science; Universal. Abstrak;Sains merupakan salah satu hal yang penting dalam upaya mendekati, dan mengenal objek-objek yang ada, maka perlu dasar kesadaran diri yang benar sepeti pemahaman khudi. Sebab, arah kemodernan dengan semangat Renaisans Barat yang berkembang menjadikan Sains Modern berprilaku fregmentatif. Sehingga dimensi fisik terlepas dari dimensi metafisik yang syarat akan nilai, serta moral. Maka, penelitian ini berusaha menganalisa aspek dan sisi tertentu pada sains modern, untuk kemudian dikritisi dengan perspektif dari khudi Muhammad Iqbal Penelitian merupakan library research dengan menggunakan pendekatan filosofis secara analisis-kritis, atas data-data. Hasil penelitian ini menyatakan bahwa Khudi Muhammad Iqbal memiliki pengaruh yang komperhensif-Integral pada diri seseorang dengan tinjauan kesadarannya. Sehingga, itu membawa keuniversalan, pertimbangan bijak, dan keterkaitan hidup yang baik dari basis filosofis, terutama bagi tren sains era ini yang dipakai sebagai rujukan hidup yang modern.Kata Kunci: Khudi; Modern; Renaisans; Sains; Universal.